2002
DOI: 10.1109/tsp.2002.803322
|View full text |Cite
|
Sign up to set email alerts
|

Performance of multiantenna signaling techniques in the presence of polarization diversity

Abstract: Multiple-input multiple-output (MIMO) antenna systems employ spatial multiplexing to increase spectral efficiency or transmit diversity to improve link reliability. The performance of these signaling strategies is highly dependent on MIMO channel characteristics, which, in turn, depend on antenna height and spacing and richness of scattering. In practice, large antenna spacings are often required to achieve significant multiplexing or diversity gain. The use of dual-polarized antennas (polarization diversity) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
133
0
6

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(143 citation statements)
references
References 23 publications
4
133
0
6
Order By: Relevance
“…The increase in RSSI relative to the omni-directional case is due to the higher antenna gain, while the increase in throughput is achieved (with the use of SM rather than STBC) through further de-correlation of the received fading envelopes by incorporating orthogonal polarization in addition to the 10λ antenna spacing on the roof of the vehicle. Similar benefits from the use of dual polarized antennas were reported by Nabar et al in [15] via simulation.…”
Section: B Capacity Enhancementsupporting
confidence: 83%
See 1 more Smart Citation
“…The increase in RSSI relative to the omni-directional case is due to the higher antenna gain, while the increase in throughput is achieved (with the use of SM rather than STBC) through further de-correlation of the received fading envelopes by incorporating orthogonal polarization in addition to the 10λ antenna spacing on the roof of the vehicle. Similar benefits from the use of dual polarized antennas were reported by Nabar et al in [15] via simulation.…”
Section: B Capacity Enhancementsupporting
confidence: 83%
“…4 suggest that copolarized directional antennas can limit the throughput of MIMO systems in LoS conditions, this can be avoided if other techniques are employed to further de-correlate the received fading envelopes. One way to achieve this is to use orthogonal polarizations at the receiver [15], in addition to the 10λ spatial separation (employed throughout the trials). This is confirmed by the throughput and the corresponding RSSI levels shown in Fig.…”
Section: B Capacity Enhancementmentioning
confidence: 99%
“…channels [13]. Nabar et al [14] studied polarization diversity as a promising cost-and spaceeffective alternative to large antenna spacing often required in spatial diversity, while it was also shown that polarisation diversities can be exploited to increase the transmission performance of outdoor-to-indoor MIMO channels [15], and the channel capacity of indoor MIMO systems [16]. Dietrich et al [17] examined the spatial and polarization diversity of wireless handsets and reported a diversity gain of 12dB to the SNR.…”
Section: Introductionmentioning
confidence: 99%
“…With recent advances in wireless communication systems for commercial and strategic applications, the polarization diversity achieved by dual polarized antenna is explored to improve the channel capacity and link reliability [1,2]. The analysis of the uses of dual polarized antenna concludes that the polarization diversity is best suited for the urban environment with Rayleigh multipath fading channels [3,4]. The dual polarized antennas have advantage in terms of space requirement and overall system cost as compared to traditional space diversity technique.…”
Section: Introductionmentioning
confidence: 99%